Are mechanics different between male and female runners with patellofemoral pain? - Willy, R. W.; Manal, K. T.; Witvrouw, E. E.; Davis, I. S. (Medicine & Science in Sports & Exercise, 2012)
Introduction: Patellofemoral pain (PFP) has often been attributed to abnormal hip and knee mechanics in females. To date, there have been few investigations of the hip and knee mechanics of males with PFP. The purpose of this study was to compare the lower extremity mechanics and alignment of male runners with PFP with healthy male runners and female runners with PFP. We hypothesized that males with PFP would move with greater varus knee mechanics compared with male controls and compared with females with PFP. Furthermore, it was hypothesized that males with PFP would demonstrate greater varus alignment.